Addressing Multinutrient Deficiency in crops using customized fertilizer - Dass, Anchal; Jinger, Dinesh; Kaur, Ramanjit; Kumar, S Vijaya; Kumari, Kavita (Indian Farming, 2017)
The customized fertilizer which contain both macro and micronutrients now manufactured in India are available for use in agriculture. At several places, yield increase exceeding 100% due to use of CF over traditional fertilizers has been reported by several workers. Thus region-agro-climate- and cropspecific CF should be offered to the farmers to remediate nutrient deficiencies particularly secondary and micronutrients for better crop response and higher productivity.